2021
DOI: 10.1021/acssuschemeng.1c02485
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Strategy for Biomimetic Construction of Calcium Phosphate Mineral Shells on Microbial Cells

Abstract: Biomimetic construction of functional shells on cells is highly important in modifying an engineered cell surface. Herein, we report a microbial in situ mineralization strategy using Acetobacter xylinum as a model strain to explore the interactions between cell metabolism and calcium phosphate crystallization. Mineral precipitation has been observed outside the cell walls during the metabolism of bacterial cellulose. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) results reveal that in situ min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Leveraging their excellent interplay, biomineralization has been extensively employed to enhance the stability of living cell storage and delivery [ 100 ]. For example, Sun et al [ 101 ] reported an in situ bionic construction strategy with a functional mineral shell. They first mineralized calcium phosphate in situ on the cell wall of the model strain Acetobacter xylinum , and in subsequent activity tests, they found that the artificial mineral shell could be an ideal barrier against natural toxins without interfering with normal metabolism.…”
Section: Shell Stabilization Strategy Inspired By Biomineralizationmentioning
confidence: 99%
“…Leveraging their excellent interplay, biomineralization has been extensively employed to enhance the stability of living cell storage and delivery [ 100 ]. For example, Sun et al [ 101 ] reported an in situ bionic construction strategy with a functional mineral shell. They first mineralized calcium phosphate in situ on the cell wall of the model strain Acetobacter xylinum , and in subsequent activity tests, they found that the artificial mineral shell could be an ideal barrier against natural toxins without interfering with normal metabolism.…”
Section: Shell Stabilization Strategy Inspired By Biomineralizationmentioning
confidence: 99%
“…These characteristics make BC a promising candidate for a wide range of industrial applications, including in tissue engineering, the cosmetic and paper industries, and the catalytic field. [4][5][6] In the food industry, BC was first used in a low-calorie DOI: 10.1002/mabi.202100476 dessert called Nata-de-coco by the natives of the Philippines, and is valued for its juicy mouthfeel and chewable texture. [7][8][9] Komagataeibacter (formerly named Gluconacetobacter) is an aerobic bacterium first isolated from brewing vinegar and has become a model strain for BC production.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make BC a promising candidate for a wide range of industrial applications, including in tissue engineering, the cosmetic and paper industries, and the catalytic field. [ 4–6 ] In the food industry, BC was first used in a low‐calorie dessert called Nata‐de‐coco by the natives of the Philippines, and is valued for its juicy mouthfeel and chewable texture. [ 7–9 ]…”
Section: Introductionmentioning
confidence: 99%